Accounting Information System Design in Purchasing Raw Materials at PT. Cahaya Mutiara Indah - Fatiah Putri Rindawan (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aimed to analyze and identify the accounting information system related to purchasing raw materials that runs in PT. Cahaya Mutiara Indah. Case study was employed as the research method to answer the research questions. The data used are primary and secondary data. The data collection methods were literature study which is from reviewing the literature, journals and other sources related to the topic and also from observation, interviews, and documentation. The results achieved in this study is the accounting information system purchases in PT. Cahaya Mutiara Indah still has some weaknesses  in  organizational structure, internal control and purchasing processes procedures. PT. Cahaya Mutiara Indah also does not have a written Standard Operating Procedure (SOP). The researcher proposes  some  ideas  to eliminate  these weaknesses, namely a proposal of organizational structure, the proposal of purchasing processes procedures, management policy proposals and accounting policy proposal.  The proposals are expected to  generate useful information for decision making and bring improvements to the business operations of PT. Cahaya Mutiara Indah and the system in the company can be more effective.   Key words: Accounting Information System, Purchasing, Raw Materials